Fundamentals of physics - Halliday, David (John Wiley & Sons, 2008)
No other book on the market today can match the 30-year success of Halliday, Resnick and Walker's "Fundamentals of Physics"! In a breezy, easy-to-understand style the book offers a solid understanding of fundamental physics concepts, and helps readers apply this conceptual understanding to quantitative problem solving. This book offers a unique combination of authoritative content and stimulating applications.